PENGARUH PRICE EARNING RATIO, TINGKAT SUKU BUNGA, DAN TINGKAT INFLASI TERHADAP HARGA SAHAM - Hasbiana Dalimunthe (Universitas Medan Area, 2015)
This research about the effect of the price earnings ratio, the interest rate and the rate of inflation on the price of shares in a mining company listed on the Indonesia Stock Exchange in 2012-2014. The approach used in this study is the associative approach, whereas the type of data used in this research is quantitative data in the statement of financial statements of the years in 2012-2014, and Bank Indonesia’s report on the interest rate and the inflation rate. The sample in this research amounted to 21 companies. Data analysis techniques in this research using classic assumption test, hypothesis testing, linear regression, and test the coefficient of determination. Processing of the data in this research using the software program SPSS (Statistical Package for the Social Sciens) 17.0 for Windows.The results of this research prove that the partial price earnings ratio have a significant effect on stock prices, whereas the interest rate and the inflation rate negatively affect the share price. Simultaneously price earnings ratio, the interest rate and the inflation rate significantly affect stock prices.